Late Banking Transitions : Comparing Uzbekistan to Earlier Reformers - Babasyan, Davit; Gu, Yunfan; Melecky, Martin (World Bank, Washington, DC, 2022)
Uzbekistan is one of the late transition economies. This paper compares the early experience and challenges that Uzbekistan confronts in transitioning its banking system to market principles against the earlier experience with banking transitions from Poland, Russia, and Vietnam, and other relevant evidence from the literature. To that effect, the paper uses new data on Uzbekistan’s banking sector, the data on past transition economies, and qualitative and quantitative evidence from the literature. Uzbekistan’s latest experience with banking transition generates important lessons for countries that have yet to transition. Namely, how much can a new transitioning country reasonably expect to accomplish within the medium term Which banking reforms are the most essential and how should they best be sequenced How can expectations about efficient capital reallocation be managed, access to finance made more equitable, and transition risks of financial instability be mitigated What are the complementary reforms in the real sector, especially of state-owned enterprises and the competition framework, that need to happen in tandem for the new banking market to function properly